Distribution Patterns of Endemic Reptiles in Semi-Arid Zones (Zoological Archives: An International Journal, 2022)
Semi-arid zones -- the transitional belt of dryland ecosystems between desert and mesic biomes spanning approximately 18% of Earth's terrestrial surface -- harbour extraordinary reptile endemism driven by the combination of high habitat heterogeneity, climatic stability over Quaternary glacial cycles, and geographic isolation promoting allopatric divergence. Yet the biogeographic drivers of semi-arid reptile distribution patterns, and the vulnerability of endemic species to ongoing climate-driven habitat shifts, remain poorly understood relative to better-studied vertebrate groups. This study presents the most comprehensive species distribution modelling analysis of semi-arid endemic reptiles yet conducted, combining original field survey data from 847 localities across 12 semi-arid regions on 4 continents with museum specimen occurrence records (n = 24,700 georeferenced records) and ensemble species distribution models (MaxEnt + BioClim + GLM) for 247 endemic reptile species across 8 families. Niche overlap analysis confirmed that the majority of endemics occupy highly restricted thermal niches (mean Schoener's D = 0.18 between congeneric pairs), explaining high beta-diversity and localised endemism. Current suitable habitat areas under ensemble SDM averaged 8,470 +- 4,240 km2 per species -- placing 84.7% of species below the IUCN Vulnerable criterion B1 threshold of 20,000 km2. Projected range shifts under RCP 4.5 and RCP 8.5 by 2070 indicate mean suitable habitat loss of -38.4% and -64.7% respectively, with 47.4% of species losing > 80% of current suitable habitat under the high-emissions scenario -- substantially exceeding the extinction risk projected from current IUCN Red List status for these taxa.